Islamic Legal Values in the Angkola Batak Community Marriage Onang-Onang Dance Tradition, Sumatra, Indonesia - Padil Simamora, Padlan; Difia Madina, Dinda; Adib Alfarisi, Muhammad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The issue of customary law and Islamic law is always used with a social conflict approach in society. However, the occurrence of marriage in the Angkola Batak community is interesting and unique, there is a tradition of oanng-onang poems in the marriage procession which reflects socio-cultural values. This research uses a normative juridical research type with a statute approach, namely examining norms, both from the shari'a and customary law aspects, and a comparative approach, namely a comparative approach between customary law and shari'a and the source of legal material in the form of nash. The results of this study show that the meaning of the Onang-Onang poem is an expression of heart longing for the mother (parents) and her lover, but it is also used in happy situations, including traditional ceremonies and contains religious values contained during the onang-onang tradition procession. Meanwhile, the authors argue that the validity of the tradition is not only socio-cultural but the religious value in Islamic law is inseparable from the role of parents and family, as well as relatives who become educational spaces in instilling attitudes and behavior in line with Islamic teachings, namely Q.S. Luqman verse 17.